A fluorescent probe for selective and instantaneous detection of hydrogen sulfide in living cells and zebrafish. (4th June 2021) - Niu, Peixin; Liu, Jiaojiao; Rong, Yifan; Liu, Xingjiang; Wei, Liuhe
Abstract: This work proposes a fluorescent probe that uses coumarin as a chromophore and NBD as a sensing unit to detect hydrogen sulfide. The probe can work well in aqueous media, and can quickly respond to hydrogen sulfide. When detecting hydrogen sulfide, the probe has high selectivity and good anti-interference ability. Besides, in monitoring hydrogen sulfide in living cells and zebrafish, good results have demonstrated the probe's potential in practical applications. Graphical abstract: A fluorescent probe that uses coumarin as a chromophore and NBD as a sensing unit to selectively and instantaneously was developed to detect hydrogen sulfide in living cells and zebrafish. Image 1 Highlights: This probe exhibited high selectivity and strong anti-interference ability in detecting hydrogen sulfide. This probe was successfully used for imaging endogenous and exogenous H2 S in living cells. The successful detection of H2 S in zebrafish proves that this probe can perform well in biological imaging.